Anticoagulant chitosan-kappa-carrageenan composite hydrogel sorbent for simultaneous endotoxin and bacteria cleansing in septic blood. (1st September 2020) - Li, Yupei; Li, Jiameng; Shi, Zhenqiang; Wang, Yilin; Song, Xin; Wang, Liya; Han, Mei; Du, Heyue; He, Chao; Zhao, Weifeng; Su, Baihai; Zhao, Changsheng
Highlights: Chitosan-carrageenan composite hydrogels were prepared via phase inversion technique. The composite hydrogels removed endotoxin in septic blood significantly. The composite hydrogels could also lower S. aureus and E. coli loads in septic blood. A novel strategy to combat sepsis by cleansing endotoxin and bacteria was proposed. Abstract: Here, we describe a green approach to fabricate genipin crosslinked chitosan-kappa-carrageenan composite hydrogels (C-K hydrogels) aiming at reducing endotoxin level and bacteria burden in septic blood synchronously. The chemical compositions and morphologies of the developed C-K hydrogels were characterized by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and scanning electron microscopy. The C-K hydrogels significantly inhibited adverse blood-material interactions such as hemolysis, complement activation, platelet activation and contact activation, and exhibited better anticoagulant properties than raw chitosan hydrogels. Most importantly, the optimized C2 -K1 hydrogels were competent to eliminate 63.3 % of endotoxin in septic blood with a maximum adsorption capacity of 95.0 EU/g during a 3-h simulative hemoperfusion procedure. Bacteria cleansing experiments further demonstrated that the optimized C2 -K1 hydrogels effectively decreased 46.0 % of E. coli and 68.7 % of S. aureus load, respectively. It is believed that the C-K hydrogels are promising hemoperfusion sorbents to treat severe septic patients.